Mechanics Model for Inclinometer Deformation in Soft Soil and Improvement of the Measurement Method - Dengheng Zheng; Liansheng Tang; Yuxi Wang; Yang Chen (Advances in Civil Engineering)
In practical engineering, data of lateral deformation in field soft soil are measured by inclinometers. Error is always present in soft soil deformation surveys due to rigidity differences and other objective factors, which means that the measured data do not reflect the actual amount of soft soil deformation. Therefore, the forces acting on an inclinometer when soft soil deforms and the difference between the soft soil deformation and the inclinometer deformation were analyzed during this study. A mechanics model for inclinometer deformation in soft soil under different geological conditions was developed, and inclinometer deflection equations were obtained, which can be used to calculate quite accurately the maximal deformation of an inclinometer. Combined with monitoring data of an inclinometer tube in the field, this model can be used to determine whether the soft soil completely bypasses the inclinometer pipe, resulting in a complete distortion of the data measured by the inclinometer tube. On this basis, an improved method for performing inclinometer pipe measurements was proposed, recommending that a new inclinometer be inserted to continue the observations when the original inclinometer reaches its ultimate strain.